A case study on bid rigging in centralized procurement of audit consulting services in Italy. Issue 2 (17th March 2022) - Albano, Gian Luigi; Santocchia, Maria Grazia
Abstract : Purpose: The aim of this case study is to review the in-depth (and successful) investigation carried out in 2016 by the Italian Competition Authority [Autorità Garante della Concorrenza e del Mercato (AGCM)] on a nation-wide (multi-lot) framework agreement for consulting services. We also critically assess the tender design and emphasize which dimensions may have facilitated the uncovered anticompetitive agreement. Design/methodology/approach: The case study borrows from the official Antitrust Authorities' findings and from the tender documents to paint a comprehensive picture of the cartel's strategy. Findings: The case study emphasizes that AGCM's the "conjectured logic" of the cartel's behaviour (endogenous evidence) did coincide with those pieces of evidence seized by police forces for criminal crimes at the cartel members' premises (exogeneous evidence). This infrequent feature of bidding rings investigations underlines the importance of theoretical as well as practical analyses of cartels' behaviour in public procurement markets. Social implications: As the antitrust investigation was triggered by a confidential report sent by the awarding authority (Consip, the Italian national central purchasing body), the case study also emphasizes the importance of informal as well as formal co-operation between awarding authorities, especially central purchasing bodies, and competition authorities. Originality/value: The case study belongs to a small set of applied research papers attempting at building a bridge between public procurement design, particularly of sizeable framework agreements, and the mechanisms devised by cartels to "game" procurement procedures. All this is accomplished by looking at all design dimensions that were exploited by cartel's members.